Discovery of repurposing drug candidates for the treatment of diseases caused by pathogenic free-living amoebae. - Christopher A Rice; Beatrice L Colon; Emily Chen; Mitchell V Hull; Dennis E Kyle (PLoS Neglected Tropical Diseases, 2020)
Diseases caused by pathogenic free-living amoebae include primary amoebic meningoencephalitis (Naegleria fowleri), granulomatous amoebic encephalitis (Acanthamoeba spp.), Acanthamoeba keratitis, and Balamuthia amoebic encephalitis (Balamuthia mandrillaris). Each of these are difficult to treat and have high morbidity and mortality rates due to lack of effective therapeutics. Since repurposing drugs is an ideal strategy for orphan diseases, we conducted a high throughput phenotypic screen of 12,000 compounds from the Calibr ReFRAME library. We discovered a total of 58 potent inhibitors (IC50 <1 μM) against N. fowleri (n = 19), A. castellanii (n = 12), and B. mandrillaris (n = 27) plus an additional 90 micromolar inhibitors. Of these, 113 inhibitors have never been reported to have activity against Naegleria, Acanthamoeba or Balamuthia. Rapid onset of action is important for new anti-amoeba drugs and we identified 19 compounds that inhibit N. fowleri in vitro within 24 hours (halofuginone, NVP-HSP990, fumagillin, bardoxolone, belaronib, and BPH-942, solithromycin, nitracrine, quisinostat, pabinostat, pracinostat, dacinostat, fimepinostat, sanguinarium, radicicol, acriflavine, REP3132, BC-3205 and PF-4287881). These compounds inhibit N. fowleri in vitro faster than any of the drugs currently used for chemotherapy. The results of these studies demonstrate the utility of phenotypic screens for discovery of new drugs for pathogenic free-living amoebae, including Acanthamoeba for the first time. Given that many of the repurposed drugs have known mechanisms of action, these compounds can be used to validate new targets for structure-based drug design.